Tradisi Jolenan Di Desa Somongari Kecamatan Kaligesing Kabupaten Purworejo - Anggun Rafiqah Aushaf (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractPurworejo is one of the districts in Central Java which is rich in natural and human resources. One of the various regional cultural traditions that is still preserved in Purworejo Regency, precisely in Somongari Village, Kaligesing District is merti-deso or village-cleansing and commonly called Jolenan. This study was dissected using a qualitative method with an ethnographic communication approach. For the deepening of the analysis observations and interviews were conducted with respondents who were involved in the Jolenan Customary Ceremony. The results showed that the communicative situation in the Jolenan Customary Ceremony was walking in a sacred manner. The traditional Jolenan ceremony is a tradition that is carried out every two years on the Javanese calendar, Seloso Wage Day in Sapar Month. Communicative events in Jolenan Traditional Ceremony are traditions that contain myths in them. Broadly speaking, the purpose of the Jolenan Traditional Ceremony is as an expression of gratitude and thanks to Allah SWT for the abundant produce of the earth and also as a tribute to the ancestors of the Sumongari Village, Eyang Kedono-Kedini. In the Jolenan Customary Rite there are ten stages in it namely: environmental cleanliness and tombs, making and decorating Jolen, tirakatan night, festivity of the Rukun Tetangga, installation of offerings, performing arts, welcoming events, Jolen carnival, large festivals, and tayuban. Communicative actions in the Jolenan Customary Ceremony namely regarding the statement of the people of Sumongari Village on the crops given by Allah SWT and the request of the people of Sumongari Village so that the village occupied is always given an abundance of crops continuously.Keywords: Traditional Communication, Jolenan Traditional Ceremony, values, social, religious, symbolic AbstrakPurworejo merupakan salah satu kabupaten di Jawa Tengah yang kaya akan sumber daya alam dan manusianya. Satu dari berbagai tradisi kebudayaan daerah yang sampai saat ini masih dilestarikan di Kabupaten Purworejo, tepatnya di Desa Somongari, Kecamatan Kaligesing adalah merti-deso atau bersih-desa dan biasa disebut Jolenan. Penelitian ini dibedah menggunakan metode kualitatif dengan pendekatan etnografi komunikasi. Untuk pendalaman analisis dilakukan observasi dan wawancara dengan para responden yang berperan dalam Upacara Adat Jolenan. Hasil penelitian menunjukkan bahwa situasi komunikatif dalam Upacara Adat Jolenan yaitu berjalan dengan sakral. Upacara adat Jolenan merupakan tradisi yang dilakukan setiap dua tahun sekali pada penanggalan Jawa yaitu hari Seloso Wage pada Bulan Sapar. Peristiwa komunikatif dalam Upacara Adat Jolenan merupakan tradisi yang mengandung mitos di dalamnya. Secara garis besar tujuan dilakukannya Upacara Adat Jolenan yaitu sebagai ungkapan rasa syukur dan terima kasih kepada Allah SWT atas hasil bumi yang melimpah dan juga sebagai penghormatan kepada leluhur Desa Sumongari yaitu Eyang Kedono-Kedini. Dalam ritual Upacara Adat Jolenan terdapat sepuluh tahapan di dalamnya yaitu: kebersihan lingkungan dan makam, membuat dan menghias Jolen, malam tirakatan, kenduri Rukun Tetangga, pemasangan sesaji, pentas kesenian, acara sambutan, kirab Jolen, kenduri besar, dan tayuban. Tindak komunikatif dalam Upacara Adat Jolenan yaitu mengenai pernyataan masyarakat Desa Sumongari atas hasil bumi yang diberikan Allah SWT dan permohonan masyarakat Desa Sumongari agar desa yang ditempati selalu diberikan kelimpahan hasil bumi secara terus menerus.Kata kunci: Komunikasi Tradisional, Upacara Adat Jolenan, nilai, sosial, religious, simbiolik